Risk and Return Analysis of Commercial Banks of Nepal (with reference to NABIL and NIBL) - Kandel, Laxman Raj (Pravaha, 2018)
This paper analyze the risk and return on common stock investment of Nepalese stock market and it is focused on common stock of two commercial banks listed in Nepal stock exchange Limited. Investors have varying perception towards risk and enterprising activities. They invest in those opportunities which have certain degree of risk associated with it. This research study found that there is a positive relationship between risk and return. Most of the investors are risk averter. It suggest to construct appropriate portfolio instead of investment in a single security which would be able to reduce unsystematic or diversifiable risk. The secondary data which was collected from NEPSE website (www.nepalstock.com), previous studies, NRB publications and publication of selected commercial banks, website of security board of Nepal (SEBO), Journals and internet. Both quantitative and qualitative analysis has been analyzed by using scientific methods. After the analysis of risk and return of sample bank and based on the past data of their last five fiscal years i.e. (FY-2012/13 to FY-2016/17), it is concluded that all the commercial banks are very much risky with fluctuated rate of return. From the findings of beta coefficient of each sample bank, the C.S. of NABIL is seems very much volatile than NIBL stock. It was also found that both selected bank have a high proportion of unsystematic risk. Pravaha Vol. 24, No. 1, 2018, Page: 109-119